Medios de transporte, accidentes de tránsito y legislación en Medellín (Colombia) durante las tres primeras décadas del siglo XX (2012)
ABSTRACT: Automobiles, cars, trucks and trains appeared in Medellín, Colombia, during the first decades of the 20th century, and affected the routines of the inhabitants who had the need to use them, thus transforming the dynamics of the city. In this process, men and women were involved in unfortunate circumstances in which these machines were the means through which people were run over. Since this act was qualified as a committed crime, it was necessary to enforce the laws and even generate legal strategies for consistently attempt these disputes. The aim of this article is to describe the ways how traffic accidents occurred in the stated context, and at the same time, relate this kind of facts with the existing legislation in that time, and the way as it was applied by the authorities when generating a verdict on the guilt of murder of a driver. For its preparation five summaries were considered by murder of the Archivo Historico Judicial de Medellín, the information of the Archivo Histórico de Medellín, and the Collection Heritage Documentary of the Unviersidad de Antioquia, articles from the local press, legislation and statistical data of that time. Keywords: urban growth, vehicles, killings, summaries, laws, modernity, accident.